Neurologic Evaluations of Patients Exposed to the World Trade Center Disaster. Issue 11 (November 2016) - Stecker, Mark M.; Yu, Huiying; Barlev, Renee; Marmor, Michael; Wilkenfeld, Marc
Abstract : Objective: The aim of this study was to describe the clinical phenotype of a limited group of responders and survivors of the World Trade Center (WTC) disaster who were referred for the evaluation of neuropathic symptoms. Methods: Sixteen patients with WTC exposure were referred to a neurologist for evaluation. All had a neurologic examination. Most had electromyogram and nerve conduction testing/nerve conduction studies as well as appropriate imaging and blood tests. Results: There was a higher probability of a neuropathy diagnosis in WTC-exposed patients than other patients referred for EMG testing. Two WTC-exposed patients had motor neuron disease and not neuropathy. Conclusion: This study provides objective evidence of neuropathy in a relatively high fraction of WTC-exposed patients with neuropathic symptoms. It also emphasizes that the scope of neurologic problems following WTC exposure may include other diagnoses such as motor neuron disease.